Analysis of Value Added Tax Payment and Reporting Calculation for Self-Building Activities - Muhtar, Muhtarudin; Nanda, Ananda Melysa Fajriyah (Journal of Accounting Inaba, 2024)
VAT on SBA is one of the roots of government revenue. In PMK No. 61/PMK.03/2022 that the action of constructing the latest building or expansion of the previous building, and not currently carrying out business/work activities is carried out for individuals/entities, the results are used by themselves or by other parties. The purpose of this observation is to find out how to calculate, deposit, and report VAT SBA with a descriptive method. The results showed that the research process on PPN SBA was carried out in 3 (three) terms. The calculation of the tax payable for SBA VAT is in line with the provisions of the tax law, namely the VAT rate of 11% multiplied by the DPP. The DPP is 20% of all costs paid during construction and does not include land prices. However, there is a difference in the calculation in determining the DPP caused by the difference in the price of building materials and building area. Deposits are made via the Perception Bank using Billing that has been created through the e-billing by requiring SSE. Deposited on January 28, so it is subject to administrative sanctions in the form of interest. Reporting is automatic at the time of deposit by obtaining proof of deposit in the form of NTPN